The Falklands (Malvinas) dispute: a critique of international law and the pacific settlement of disputes - Shucksmith-Wesley, Marc (2018)
This thesis brings a focusing lens on one of history’s most intractable and protracted territorial disputes, that between the United Kingdom and Argentina over the non-self-governing territory known as the Falklands (Malvinas), an archipelago of 200 islands, some 480 miles north-east of Cape Horn, Argentina. For Argentina, the ‘Malvinas are a constantly bleeding wound, flesh torn from the body that is Argentina’. To the United Kingdom, the territory represents one of the last vestiges of its once vast empire, having held effective control of the territory since 1833, other than for a short period in 1982 following an Argentine use of military force. The facts, history, law, and politics of this dispute all act in concert to create a picture that is so highly nebulous that a clear view as to which State should hold territorial sovereignty has yet to emerge, with there being legitimately argued positions in favour of both disputing States. At the heart of this thesis is a critical analysis of the history, the legal arguments, and the methodologies of international lawyers in order to examine the effectiveness of international law as a dispute settlement mechanism. In doing so, this thesis ascertains whether international law has a role to play in resolving this most entrenched of international disputes. This re-evaluation of the value of international law, through a critical lens, argues that international law does have the potential to assist in the resolution of the dispute. However, this is only possible if political leaders are ready to grasp on to that opportunity, and to make use of diplomatic means of dispute settlement, at the critical moment when the dispute becomes ripe, at times of significant political change. It is in these moments that international law could prove to be the guiding hand that may assist with the normalisation of relations between Argentina and the UK.